Tempo, finitude, velhice e fotografia - Justo, Joana Sanches; Justo, José Sterza [UNESP] (My University, 2012)
This article analyzes and discusses the experience of time in old age through the relations of the elderly with photography. We did photography workshops with a group of elders exploring with them the sense of the photographic act death, as an act of freezing and stopping time and also the sense of exploring the future to create, through the photographic act, an image that can symbolize moving on in life.

O presente artigo analisa e discute a experiência do tempo na velhice a partir das relações do idoso com a fotografia. Para tanto, realizamos oficinas de fotografia com um grupo de idosos, explorando com eles o sentido de morte do ato fotográfico, enquanto ato de congelamento e paralisação do tempo e também o sentido de prospecção do futuro ao poder criar, pelo ato fotográfico, uma imagem capaz de simbolizar a busca adiante na vida.
Time, Finitude, Old Age and Photography
Keywords: Time; Finitude; Old Age; Photography; Tempo; Finitude; Velhice; Fotografia